2019
DOI: 10.1016/j.actpsy.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Is planning related to dynamic testing outcomes? Investigating the potential for learning of gifted and average-ability children

Abstract: Is planning related to dynamic testing outcomes? Investigating the potential for learning of gifted and averageability children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…In conclusion, high intelligence does not always reflect faster performance (Reams, Chamrad & Robinson, 1990). In the same vein, some studies have shown an equivalent learning progression in intellectually gifted and average children (Vogelaar, Bakker, Elliott, & Resing, 2017a;2017b;Vogelaar, Resing, Stad, & Sweijen, 2019). Although there are some contradictory results (Calero, Belen, & Robles, 2011;Kanevsky & Geake, 2004), the rapidity to learn in IGC seems not to distinguish from IAC in the potential of learning.…”
Section: Attentional Network In Gifted Children !mentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, high intelligence does not always reflect faster performance (Reams, Chamrad & Robinson, 1990). In the same vein, some studies have shown an equivalent learning progression in intellectually gifted and average children (Vogelaar, Bakker, Elliott, & Resing, 2017a;2017b;Vogelaar, Resing, Stad, & Sweijen, 2019). Although there are some contradictory results (Calero, Belen, & Robles, 2011;Kanevsky & Geake, 2004), the rapidity to learn in IGC seems not to distinguish from IAC in the potential of learning.…”
Section: Attentional Network In Gifted Children !mentioning
confidence: 99%
“…Although there are some contradictory results (Calero, Belen, & Robles, 2011;Kanevsky & Geake, 2004), the rapidity to learn in IGC seems not to distinguish from IAC in the potential of learning. The specificity of intellectual giftedness concerns on the high capacity to learn and to generalize their newly acquired knowledge in other contexts (Calero et al, 2011;Vogelaar et al, 2017aVogelaar et al, , 2017bVogelaar et al, , 2019. This high learning capacity might be tied to their high performance in reasoning (Caropreso & White, 1994), working memory (Calero, García-Martín, Jiménez, Kazén, & Araque, 2007;Hoard, Geary, Byrd-Craven, & Nugent, 2008;Leikin, Paz-Baruch, & Leikin, 2013;van Viersen, Kroesbergen, Slot, & de Bree, 2014), metacognitive abilities (Oppong, Shore, Muis, 2019) and executive functions (Arffa, 2007).…”
Section: Attentional Network In Gifted Children !mentioning
confidence: 99%
“…Other studies have found that visuo‐spatial working memory (Resing, 2013) and metacognition (Vogelaar et al, 2017) were related to improvements in analogical reasoning after training. In a study by Vogelaar, Resing, Stad, and Sweijen (2019) it was, furthermore, found that planning predicted the number of prompts children needed in the first training session, but not the second.…”
Section: Introductionmentioning
confidence: 97%
“…The current study aimed to broaden the existing knowledge regarding the relationship between analogical reasoning and executive functioning by examining children's potential for solving analogies, using a newly developed computerized dynamic test of analogical reasoning. As dynamic testing is suggested to compensate for weaknesses in these functions (Vogelaar et al, 2017, Vogelaar et al, 2019), it was examined whether they would be differentially related to static and dynamic measures of analogical reasoning. In the test utilized in the current study, children had to construct their own answers, which was believed to provide insight into the process of task‐solving.…”
Section: Introductionmentioning
confidence: 99%
“…Applied aspects of identifying extraordinary abilities of children are studied by such scientists as Vogelaar B, Calero M., Adelson J, Smedsrud J., and others. [7][8][9][10]. Important methodological issues related to an integrated approach to the problem of giftedness, taking into account its personal components, have been posed by AK.…”
Section: Introductionmentioning
confidence: 99%